2014
DOI: 10.1039/c4cc06651k
|View full text |Cite
|
Sign up to set email alerts
|

Fructose-coated nanoparticles: a promising drug nanocarrier for triple-negative breast cancer therapy

Abstract: Fructose transporter GLUT5 is overexpressed in breast cancer cell lines, but not in healthy tissue. Micelles based on fructose, which were found to be low fouling, showed a high uptake by breast cancer cells (MCF-7 and MDA-MB-231 cells), but only negligible uptake by macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 29 publications
1
94
0
1
Order By: Relevance
“…The concentrations used are all well above the critical micelle concentration measured earlier for similar block copolymer, but with a slightly different hydrophobic block. 26 Since the PMMA core here has high kinetic stability due to the glassy core the obtained morphologies can be considered stable under these conditions. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 18 The fluorescence intensity of cells (MCF-7 and MDA-MB-231 cells) as shown in Figure 4 indicates that the amount of short rods (length around 500 nm) internalized by cells is significantly higher than that of medium (length around 1000 nm) and long ones (length around 2000 nm).…”
Section: Length Effect Of Rods On Cellular Uptake By Breast Cancer Cementioning
confidence: 99%
See 2 more Smart Citations
“…The concentrations used are all well above the critical micelle concentration measured earlier for similar block copolymer, but with a slightly different hydrophobic block. 26 Since the PMMA core here has high kinetic stability due to the glassy core the obtained morphologies can be considered stable under these conditions. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 18 The fluorescence intensity of cells (MCF-7 and MDA-MB-231 cells) as shown in Figure 4 indicates that the amount of short rods (length around 500 nm) internalized by cells is significantly higher than that of medium (length around 1000 nm) and long ones (length around 2000 nm).…”
Section: Length Effect Of Rods On Cellular Uptake By Breast Cancer Cementioning
confidence: 99%
“…26 Briefly, D-fructose (36 g, 200 mmol) was dissolved in a cooled solution of sulfuric acid (35 ml, 98%) in acetone (700 mL) and stirred at room temperature for 90 min.…”
Section: Synthesis Of 1-o-methacryloyl-23:45-di-o-isopropylidene-β-mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Glycosylation is one of the promising approaches for active targeted delivery due to the inherent biocompatibility and bioadhesiveness of sugar molecules and the pivotal roles of carbohydrate recognition mechanisms in major biological events. 16 Studies have reported functionalization with terminal fructopyranose moieties for breast cancer cells targeting, 17 and mannose as specific ligand for immune scavenge cells such as macrophages and dendritic cells. 18,19 Moreover, glycosylated nanocarriers with terminal galactose or lactose moieties have also shown selectivity for hepatic cells, with clinical relevance for hepatoma chemotherapy or hepatitis C treatment.…”
Section: Lou Et Almentioning
confidence: 99%
“…[45][46][47][48][49] Theses trategies have deliverede xcellent peptides and relateda naloguesw ith applications in gene delivery, liposomef unctionalization, nanoparticle decoration, and therapeutic protein delivery. [43,[64][65][66][67][68][69][70][71] This strategy is aimed at targeting cellular membrane receptors and accumulatingg lycan-tagged ensembles at ap articular tissue. [59][60][61][62] For instance, the cationic charactero fC PPs, which is required form embrane anchoring and translocation, constitutes an important drawback because highly cationic molecules tend to stick nonspecifically in living tissues.…”
Section: Introductionmentioning
confidence: 99%